Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 10 - Exponents and Radicals - 10.8 The Complex Numbers - 10.8 Exercise Set - Page 686: 26



Work Step by Step

Using the Product Rule of radicals which is given by $\sqrt[m]{x}\cdot\sqrt[m]{y}=\sqrt[m]{xy},$ and $i=\sqrt{-1},$ the given expression is equivalent to \begin{array}{l}\require{cancel} \sqrt{-72}-\sqrt{-25} \\\\= \sqrt{-1}\cdot\sqrt{72}-\sqrt{-1}\cdot\sqrt{25} \\\\= i\sqrt{72}-i\sqrt{25} .\end{array} Extracting the root of the factor that is a perfect power of the index results to \begin{array}{l}\require{cancel} i\sqrt{72}-i\sqrt{25} \\\\= i\sqrt{36\cdot2}-i\sqrt{25} \\\\= i\sqrt{(6)^2\cdot2}-i\sqrt{(5)^2} \\\\= i\cdot6\sqrt{2}-i\cdot5 \\\\= 6i\sqrt{2}-5i .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.